Sampling for Soil Carbon Stock Assessment in Rocky Agricultural Soils. Issue 5 (30th August 2016) - Beem-Miller, Jeffrey P.; Kong, Angela Y.Y.; Ogle, Stephen; Wolfe, David
Abstract : Core Ideas: Soil mass is the greatest source of uncertainty for C stocks on rocky soils. Coring methods underestimate soil rock fragment content. Hammer coring methods underestimate soil mass. Mass‐based C stock reporting can overcome coring method bias. Rotary corers are a cost‐competitive and less biased alternative to standard corers. Coring methods commonly employed in soil organic C (SOC) stock assessment may not accurately capture soil rock fragment (RF) content or soil bulk density (ρb ) in rocky agricultural soils, potentially biasing SOC stock estimates. Quantitative pits are considered less biased than coring methods but are invasive and often cost‐prohibitive. We compared fixed‐depth and mass‐based estimates of SOC stocks (0.3‐m depth) for hammer, hydraulic push, and rotary coring methods relative to quantitative pits at four agricultural sites ranging in RF content from <0.01 to 0.24 m 3 m −3 . Sampling costs were also compared. Coring methods significantly underestimated RF content at all rocky sites, but significant differences ( p < 0.05) in SOC stocks between pits and corers were only found with the hammer method using the fixed‐depth approach at the <0.01 m 3 m −3 RF site (pit, 5.80 kg C m −2 ; hammer, 4.74 g C m −2 ) and at the 0.14 m 3 m −3 RF site (pit, 8.81 kg C m −2 ; hammer, 6.71 kg C m −2 ). The hammer corer also underestimated ρb at all sites as did the hydraulic push corer at the 0.21 m 3 m −3 RF site. No significant differences in mass‐based SOC stock estimates were observed between pits and corers. Our results indicate that (i) calculating SOC stocks on a mass basis can overcome biases in RF and ρb estimates introduced by sampling equipment and (ii) a quantitative pit is the optimal sampling method for establishing reference soil masses, followed by rotary and then hydraulic push corers.